2010
DOI: 10.1007/s00066-010-2067-8
|View full text |Cite
|
Sign up to set email alerts
|

Dose Escalation in Patients Receiving Whole-Brain Radiotherapy for Brain Metastases from Colorectal Cancer

Abstract: These data suggest that patients with brain metastases from colorectal cancer treated with WBRT alone appeared to benefit from escalation of the radiation dose beyond 10 x 3 Gy in terms of improved OS and LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
3
17
2
Order By: Relevance
“…Moreover, Jung and Kruser reported a similar relationship between the shorter interval of diagnosis and the better survival outcomes in patient with BM from CRC [8,9]. Similarly, the presence of concurrent extracranial metastases has also been reported to be significantly associated with poor prognosis after aggressive treatment for patients with BM from CRC [20][21][22]. However, in the present study, longer intervals and the presence of extracranial metastases were not negatively associated with survival in this study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Moreover, Jung and Kruser reported a similar relationship between the shorter interval of diagnosis and the better survival outcomes in patient with BM from CRC [8,9]. Similarly, the presence of concurrent extracranial metastases has also been reported to be significantly associated with poor prognosis after aggressive treatment for patients with BM from CRC [20][21][22]. However, in the present study, longer intervals and the presence of extracranial metastases were not negatively associated with survival in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been suggested that a limited number of brain lesions is correlated with a favorable clinical outcome [10,18,20,28]. On the contrary, Kruser and colleagues [9] found that the presence of more than three brain metastases was a positive prognostic factor.…”
Section: Discussionmentioning
confidence: 95%
“…In agreement with the reports of other authors, in the treatment of our group of patients with HM to the brain, surgery, stereotactic radiotherapy, WBPR, and WBRT were used [14,15,18,22,26,32,33,36,38,43,46,49,50]. The median survival of 10 patients was 4 months (range, 1-68 months); 2 patients treated with surgical resection and WBRT survived 60 months.…”
Section: Hm To the Brainsupporting
confidence: 74%
“…Simultaneous brain metastases are diagnosed in half of the patients [16]. However, the prognosis is determined by LMC, since survival after brain metastases exceeds that of LMC by several fold [9,14,20] Current treatment recommendations predominately based on retrospective series comprise chemotherapy, radiotherapy, or both modalities. Chemotherapy is given intravenously (i.v.)…”
mentioning
confidence: 99%